Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratio in Univentricular Patients From Birth to Follow-Up After Fontan—Predicting Lymphatic Abnormalities - Moosmann, Julia; Schroeder, Christian; Cesnjevar, Robert; Rottermann, Kathrin; Weigelt, Annika; Dittrich, Sven (Frontiers in Pediatrics, 2021)
Background Reliable biomarkers identifying complications after Fontan surgery including the lymphatic abnormalities and the development of protein-losing enteropathy (PLE) are rare. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocte ratio (PLR) are inflammatory biomarkers and have been studied to predict outcome and prognosis in various diseases. The aim of this study was to investigate NLR and PLR from birth to follow-up after Fontan and evaluate their use as prognostic parameters for single ventricle patients regarding the development of lymphatic malformations during follow-up. Material and Methods 66 univentricular patients who underwent Fontan surgery and had 6-month follow-up magnetic resonance imaging (MRI) with T2 weighted lymphatic imaging after total cavopulmonary connection (TCPC) surgery were included in the study. NLR and PLR were determined at specific time points, from neonatal age to follow-up after Fontan operation and correlated to data from the MRI 6 months after Fontan. Results NLR and PLR increase significantly over time from the first surgery during infancy to the follow-up after Fontan (both p<0.0001), with a significant increase after the Glenn surgery for both ratios (each p<0.0001). Higher NLR (p=0.002) and higher PLR (p=0.004) correlated with higher-grade classification of lymphatic abnormalities in T2-weighted imaging 6 months after Fontan surgery and higher NLR correlated with higher transpulmonary gradient prior to Fontan surgery (p=0.035) Both ratios showed a significant correlation to total protein at follow-up (NLR p=0.0038; PLR<0.0001). Conclusion Increased NLR and PLR correlate with higher degree lymphatic malformations after TCPC and therefore might contribute as valuable additional biomarker during follow-up after TCPC. NLR and PLR are simple, inexpensive and easily available parameters to complement diagnostics after TCPC.